MONSTROUS MATERNAL FIGURES: FEMINIST HORROR ANALYSIS OF EVIL DEAD RISE PRODUCED BY SAM RAIMI - Darien Julian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The representation of mothers in horror cinema frequently embodies ambivalence by presenting maternal figures that depart from idealized constructions of motherhood. This study examines the character of Ellie in Evil Dead Rise (2023), directed by Lee Cronin, as a monstrous maternal figure that signifies the inversion of maternal roles within the domestic sphere. Employing a qualitative descriptive–interpretative approach, the analysis draws on visual scenes and dialogues as primary data, supported by feminist horror theory as secondary sources. The findings demonstrate that Ellie is constructed as a monstrous maternal figure through the distortion of nurturing functions, the collapse of maternal protection, and the portrayal of the maternal body as a locus of horror and violence. Her transformation into a demonic entity fractures familial bonds and reconfigures the domestic space as a site of terror. The study concludes that Evil Dead Rise situates motherhood at the core of horror to articulate cultural anxieties surrounding maternal roles and responsibilities, illustrating how contemporary horror mobilizes the maternal figure as a vehicle for feminist critique. ABSTRAK Representasi ibu dalam film horor kerap menghadirkan ambivalensi dengan menampilkan figur maternal yang menyimpang dari idealisasi peran keibuan. Penelitian ini menganalisis karakter Ellie dalam Evil Dead Rise (2023) karya sutradara Lee Cronin sebagai figur ibu monstrus yang merefleksikan pembalikan fungsi-fungsi maternal dalam ruang domestik. Dengan menggunakan pendekatan kualitatif deskriptif–interpretatif, penelitian ini mengkaji adegan visual dan dialog sebagai data utama, yang didukung oleh teori horor feminis sebagai data sekunder. Hasil penelitian menunjukkan bahwa Ellie direpresentasikan sebagai figur maternal monstrus melalui pembalikan peran pengasuhan, pengikisan fungsi perlindungan ibu, serta penggambaran tubuh maternal sebagai sumber kengerian dan kekerasan. Transformasinya menjadi entitas demonik merusak relasi kekeluargaan dan mengubah ruang domestik menjadi medan teror. Penelitian ini menyimpulkan bahwa Evil Dead Rise menempatkan sosok ibu sebagai pusat horor untuk mengekspresikan kecemasan kultural terkait peran dan tanggung jawab keibuan, sekaligus menunjukkan bagaimana horor kontemporer memanfaatkan figur maternal sebagai medium kritik feminis.